The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1172/jci67225
|View full text |Cite
|
Sign up to set email alerts
|

Iron regulation by hepcidin

Abstract: Discovery and function of hepcidin in iron homeostasisHepcidin is a key peptide hormone that regulates iron homeostasis in chordates. Hepcidin was initially characterized as an antimicrobial peptide in a mass spectrometry-based search for cysteine-rich defensin-like peptides in blood (1) and in urine (2). However, both groups showed that hepcidin displays only a weak antimicrobial activity. Further, unlike defensins, which vary in sequence among species, hepcidin is highly conserved from zebrafish to humans. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 123 publications
3
167
0
7
Order By: Relevance
“…Conversely, several studies have shown that iron deprivation inhibits in vitro tumor growth (15). Hepcidin is a key peptide hormone that regulates iron homeostasis in chordates and is produced by the liver in response to inflammatory stimuli and iron overload (16,17). Hepcidin is a small antimicrobial peptide that inhibits iron absorption by enterocytes, iron release from macrophages, and iron transport across the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, several studies have shown that iron deprivation inhibits in vitro tumor growth (15). Hepcidin is a key peptide hormone that regulates iron homeostasis in chordates and is produced by the liver in response to inflammatory stimuli and iron overload (16,17). Hepcidin is a small antimicrobial peptide that inhibits iron absorption by enterocytes, iron release from macrophages, and iron transport across the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…110 The mechanism may involve a decreased production or sensitivity to erythropoietin, 20 inhibition of erythroid precursors 13 and disruption of the iron metabolism mediated by hepcidin. 111 Basseri et al 112 showed a correlation between high levels of IL-6, hepcidin and ferritin and the severity of anaemia.…”
Section: Rationalementioning
confidence: 99%
“…В ОАК: Эр -3,2*10 12 /л, Hb -91 г/л, Т -258*10 9 /л (N: 150-390), Л -3,8*10 9 /л, лимфо-циты -14% (18-40) / 0,5*10 9 /л (1,2-3,0), п/я -7%, с/я -75%, СОЭ -69 мм/час, ретикулоциты -6 промилле (N: 2-13), просмотр окрашенного мазка периферической крови: гипохромия эритроцитов (++), анизоцитоз смешанный (+), встречаются мега-лоциты и гипохромные макроциты; ОАМ: цвет -жёлтая, прозрачность -мутная, относительная плотность 1010 (N: 1012-1024), реакция -кислая, белок -4,6 г/л (N: 0-0,12), глюкоза -нет, эпите-лий плоский -2-3 в п/з, цилиндры зернистые, вос-ковидные, лейкоцитарные -ед. в п/з, бактерии (+); показателей БАК: глюкоза -7 ммоль/л (N: до 5,5), общий белок -49 г/л (65-85), альбумины -43,6% (46,9-61,4), α 1 -gl -5,31% (2,(2)(3)(4)2), α 2 -gl -15,8% (7,(9)(10)9), β-gl -14,6% (10,2-18,3), γ-gl -20,7% (17,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)4), общий билирубин -9,7 мкмоль/л, прямой би-лирубин -2,2 мкмоль/л, ЩФ -157 Ед/л (до 270), ГГТП -61 Ед/л (до 32), креатинин -128 мкмоль/л (до 106), мочевина -11,6 ммоль/л (до 8,3), мочевая кислота -732 мкмоль/л (до 310), сывороточное железо -4,9 мкмоль/л (6,1), ПТИ -103% (80-110), уровни АЛТ и АСТ -в N; определены уровни прокальцитонина -0,23 нг/мл (до 0,5) и сывороточ-ного ферритина -887 мкг/л (15-150), кровь на си-филис (ЭДС) -отрицательно. ОАМ в динамике на 3 сутки: относительная плот-ность -1003, реакция -кислая, белок -1,9 г/л (0-0,12), лейкоциты -45-55 в п/з, эритроциты из-менённые -10-15 в п/з, глюкоза -нет, эпителий плоский -ед.…”
unclassified